Lithological and structural control on fracture frequency distribution within a carbonate-hosted relay ramp. (August 2020) - Mercuri, Marco; Carminati, Eugenio; Tartarello, Maria Chiara; Brandano, Marco; Mazzanti, Paolo; Brunetti, Alessandro; McCaffrey, Ken J.W.; Collettini, Cristiano
Abstract: Understanding the factors controlling fracture frequency distribution can greatly improve the assessment of fluid circulation in fault damage zones, with evident implications for fault mechanics, hydrogeology and hydrocarbon exploration. This is particularly important for relay zones that are usually characterized by strong damage and structural complexity. We investigated the fracture frequency within an outcrop adjacent to the front fault segment of a relay ramp, hosted within peritidal carbonates that forms part of the Tre Monti fault (Central Italy). We analysed the distribution of fracture frequency in the outcrop through (1) scanlines measured in the field, (2) oriented rock samples, and (3) scan-areas performed on a virtual outcrop model. Fracture frequency increases with distance from the front segment of the relay ramp. Moreover, supratidal and intertidal carbonate facies exhibit higher fracture frequency than subtidal limestones. This trend of increased fracture frequency has two main explanations. (1) The number of subsidiary faults and their associated damage zones increases moving away from the front segment. (2) The supratidal and intertidal carbonate facies content increases toward the centre of the relay ramp. Our results indicate that the fracture frequency pattern is very complex in relay ramps hosted in shallow-water limestones and that its prediction necessitates a good control on structures and sedimentary facies distribution. Highlights: Analysis of fracture distribution within a carbonate-hosted relay ramp. Integration of scanlines, oriented rock samples and a virtual outcrop model. Fracture frequency increases with distance from the front segment of the relay ramp. Subsidiary faults and carbonate peritidal facies control fracture distribution.